Odpowiedzi

2009-11-15T20:46:16+01:00
2√9/4√3=2√9/4√3 * √3/√3= 2√27/12=√27/6

3-√5/2+3√5=3-√5/2+3√5* 2-3√5/2-3√5=6-9√5-2√5+15/4-15=-(21-11√5/11)
Najlepsza Odpowiedź!
2009-11-15T20:47:41+01:00
A) 2√9/4√3=2√9*√3/4√3*√3=2√27/4*3=2*3√3/12=6√3/12=√3/12

b) 3-√5/2+3√5=(3-√5)(2-3√5)/(2+3√5)(2-3√5)=6-9√5-2√5+15/4-9*5=
21-11√5/4-45=21-11√5/-41
2009-11-15T20:52:33+01:00
A) 2√9/4√3 =
2√9/4√3 × -4√3/-4√3 =
(2√9)(-4√3)/(4√3)(-4√3) =
8√27/-16√9=
8√27/-16×3=
8√27/-48

b)3-√5/2+3√5=
3-√5/2+3√5×2-3√5/2-3√5=
(3√5)(2-3√5)/(2+3√5)(2-3√5)=
6√5-9√25/4-6√5+6√5-9√25=
6√5-45/4-45=
6√5-45/-41